2010
DOI: 10.1105/tpc.110.073908
|View full text |Cite
|
Sign up to set email alerts
|

Y3IP1, a Nucleus-Encoded Thylakoid Protein, Cooperates with the Plastid-Encoded Ycf3 Protein in Photosystem I Assembly of Tobacco and Arabidopsis    

Abstract: The intricate assembly of photosystem I (PSI), a large multiprotein complex in the thylakoid membrane, depends on auxiliary protein factors. One of the essential assembly factors for PSI is encoded by ycf3 (hypothetical chloroplast reading frame number 3) in the chloroplast genome of algae and higher plants. To identify novel factors involved in PSI assembly, we constructed an epitope-tagged version of ycf3 from tobacco (Nicotiana tabacum) and introduced it into the tobacco chloroplast genome by genetic transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 69 publications
3
92
0
Order By: Relevance
“…In addition, mRNA levels of genes encoding regulatory or assembly proteins for PSI biogenesis, such as hypothetical chloroplast RF3 (Ycf3, Boudreau et al, 1997;Albus et al, 2010), high chlorophyll fluorescence 101 (HCF101, , pale yellow green 7 (PYG7, Stöckel et al, 2006), Arabidopsis translation of PsaB mRNA (ATAB2, Barneche et al, 2006), Ycf3-interacting protein 1 (Y3IP1, Albus et al, 2010), and accumulation of photosystem one1 (APO1, Amann et al, 2004;Watkins et al, 2011), was the same in nox plants as in the wild (A) Nondenaturing Deriphat-PAGE separation of pigmented thylakoid complexes from wild-type (WT) and nox plants. Numbering of green bands (B1 to B7) is reported.…”
Section: Lower Abundance Of Psi In Nox Leaves Resulted From a Combinamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, mRNA levels of genes encoding regulatory or assembly proteins for PSI biogenesis, such as hypothetical chloroplast RF3 (Ycf3, Boudreau et al, 1997;Albus et al, 2010), high chlorophyll fluorescence 101 (HCF101, , pale yellow green 7 (PYG7, Stöckel et al, 2006), Arabidopsis translation of PsaB mRNA (ATAB2, Barneche et al, 2006), Ycf3-interacting protein 1 (Y3IP1, Albus et al, 2010), and accumulation of photosystem one1 (APO1, Amann et al, 2004;Watkins et al, 2011), was the same in nox plants as in the wild (A) Nondenaturing Deriphat-PAGE separation of pigmented thylakoid complexes from wild-type (WT) and nox plants. Numbering of green bands (B1 to B7) is reported.…”
Section: Lower Abundance Of Psi In Nox Leaves Resulted From a Combinamentioning
confidence: 99%
“…Some of the available PsaA/B mutants are either defective in the transcription of the psaA-psaB-rps14 operon (Hein et al, 2009) or in its stability ; others are impaired in the translation of the dimeric complex or cannot accumulate a stable heterodimer (Stöckel et al, 2006;Albus et al, 2010) or are affected in intron splicing of chloroplast mRNAs, including those encoding molecular chaperone-like complexes, such as Ycf3 (Landau et al, 2009;Ye et al, 2012); others are defective in the stable assembly of several [4Fe-4S] cluster-containing complexes of chloroplasts, including the PsaA/ B dimer (Schwenkert et al, 2010).…”
Section: Comparison Between Nox and Other Mutants Affected In The Biomentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent reverse genetics analysis of Y3IP1 function in tobacco and Arabidopsis revealed that the knockdown of Y3IP1 leads to a specific deficiency in PSI but does not result in loss of YCF3. Y3IP1 is loosely associated with thylakoid membranes and exists in two distinct protein complexes [42]. Unlike all other PSI assembly factors known to date, Y3IP1 appears to be newly evolved in photosynthetic eukaryotes.…”
Section: Regulatory Factors For Psi Assemblymentioning
confidence: 99%
“…Y3IP1 (YCF3-interacting protein 1), which specifically interacts with the YCF3 protein, was identified by co-immunoprecipitation with a FLAG-tagged YCF3 in transplastomic tobacco [42]. Subsequent reverse genetics analysis of Y3IP1 function in tobacco and Arabidopsis revealed that the knockdown of Y3IP1 leads to a specific deficiency in PSI but does not result in loss of YCF3.…”
Section: Regulatory Factors For Psi Assemblymentioning
confidence: 99%